142k views
0 votes
Slove the equation3 (c + 5) - 7 = 23

User Yngve
by
5.7k points

1 Answer

2 votes

Given the following equation:


3(c+5)-7=23​

Step 1. You must apply the Distributive property:


\begin{gathered} (3)(c)+(3)(5)-7=23​ \\ 3c+15-7=23 \end{gathered}

Step 2. Solve the subtraction:


3c+8=23

Step 3. Apply the Subtraction property of equality by subtracting 8 from both sides of the equation:


\begin{gathered} 3c+8-(8)=23-(8) \\ 3c=15 \end{gathered}

Step 4. Apply the Division property of equality by dividing both sides of the equation by 3:


(3c)/(3)=(15)/(3)

The solution is:


c=5

User Marduk
by
5.9k points